Species interactions: next‐level citizen science. Issue 12 (27th October 2021) - Groom, Quentin; Pernat, Nadja; Adriaens, Tim; de Groot, Maarten; Jelaska, Sven D.; Marčiulynienė, Diana; Martinou, Angeliki F.; Skuhrovec, Jiří; Tricarico, Elena; Wit, Ernst C.; Roy, Helen E.
Abstract : We envisage a future research environment where digital data on species interactions are easily accessible and comprehensively cover all species, life stages and habitats. To achieve this goal, we need data from many sources, including the largely untapped potential of citizen science for mobilising and utilising existing information on species interactions. Traditionally volunteers contributing information on the occurrence of species have focused on single‐species observations from within one target taxon. We make recommendations on how to improve the gathering of species interaction data through citizen science, which data should be collected and how it can be motivated. These recommendations include providing feedback in the form of network visualisations, leveraging a wide variety of other data sources and eliciting an emotional connection to the species in question. There are many uses for these data, but in the context of biological invasions, information on species interactions will increase understanding of the effects of invasive alien species on recipient communities and ecosystems. We believe that the inclusion of ecological networks as a concept within citizen science, not only for initiatives focussed on biological invasions but also across other ecological themes, will not only enrich scientific knowledge on species interactions but also deepen the experience and enjoyment of citizens themselves.